Polska Partia Socjalistyczna wobec problemów życia społecznego w powiecie kołobrzeskim w pierwszych miesiącach powojennych - Piecyk, Arkadiusz (Komunizm: System - Ludzie - Dokumentacja, 2023)
The subject of the article is the attitude to the problems of social life in the activities of the Polish Socialist Party (PPS) in the Kołobrzeg district just after the end of World War II. Socialist activists operated in extremely difficult conditions, facing many challenges. The article presents the struggles of PPS activists in the face of such problems as: lack of food supplies, relations with the Soviet occupation forces and the Germans remaining in these areas after the war, war damage, crime, demoralization of the Citizens’ Militia, attempts to adapt the newly seized lands to the needs of the settlers